Palladium on Charcoal Catalyzed 3,4-Hydroperoxidation of α-Substituted Enals with Triethylsilane and Water - Tuokko, Sakari; Pihko, Petri M. (Synlett, 2016)
Aldehyde α-hydroperoxides can be accessed from α-substituted acroleins with triethylsilane and water under Pd/C catalysis and aerobic conditions. The reaction is composed of a Pd/C-catalyzed conjugate reduction step and a hydroperoxidation step. The hydroperoxidation takes place via autoxidation of sufficiently stable enols formed in situ by transfer hydrogenation. Upon reduction, 2,2-disubstituted 1,2-diols are obtained directly from aldehydes.
Keywords: autoxidation; enols; palladium; oxygen; aldehydes; hydroperoxides; hydrosilylation